Using light and electron microscopy to understand the replication of aphthoviruses - Lai, PYA (2023)
Aphthovirus is a genus of the family Picornaviridae which includes Foot-and-mouth-disease virus (FMDV) and Equine rhinitis A virus (ERAV). FMDV is a highly contagious pathogen infecting cloven-hoofed animals and is hence economically important. FMDV replication takes place in the cytoplasm and induces massive rearrangement of the host cell membranes to facilitate virus replication. Rearranged membranes form structures providing the site of viral genome replication known as the replication organelle (RO). The understanding of the RO, viral proteins and site of virus assembly is not well established. This project applies various microscopy approaches to investigate details of aphthovirus replication in cells.